Crumpled particles of ethanol-wetted graphene oxide for medium-temperature nanofluidic solar-thermal energy harvesting. (January 2022) - Zhang, Jingyi; Shu, Lei; Chang, Chao; Li, Xiaoxiang; Lin, Ruiming; Fu, Benwei; Song, Chengyi; Shang, Wen; Tao, Peng; Deng, Tao
Abstract: Direct absorption of sunlight with carbon nanofluids is a facile way to efficiently harvest solar-thermal energy, but poor dispersion stability of nanofluids under elevated temperatures severely limits their applications. Herein, we report a general strategy to prepare stably-dispersed medium-temperature solar-thermal nanofluids by employing crumpled particles of ethanol-wetted graphene oxide sheets as the self-dispersible photothermal converters. The crumpled particles simultaneously possess intensively-deformed surface structure, a low density and a small particle size. Such features weaken the inter-particle van der Waals attraction and gravitational sedimentation of the crumpled particles, thereby enabling their long-term stable dispersion within commercial thermal storage oils. Uniform dispersion of nanofluids was maintained after continuous heating for 2 weeks under a heating temperature up to 200 °C. The homogenously dispersed nanofluids also achieved high solar absorptance with low particle loadings, and retained the large heat capacity and suitable viscosity. These combined advantageous thermophysical properties enabled consistent high-performance medium-temperature direct absorption-based nanofluidic solar-thermal energy harvesting under large-flux solar illumination. Graphical abstract: Image 1